MAKNA SAKIT PADA PENDERITA PENYAKIT JANTUNG KORONER: STUDI FENOMENOLOGIS - Hamzah, Imam Faisal; Dewi, Endah Kumala; Suparno, Suparno (Faculty of Psychology, Diponegoro University, 2014)
AbstractDisease is a physical dimension which is often responded subjectively by the affected individual. The interaction among biological, psychological, and social dimensions of illness can influence the illness cognition of the affected individual. This also applied to individual who suffers from a chronic illness. This study aims to describe the meaning of illness in view of patients with chronic illness. A qualitative phenomenological method was used in this study. Three subjects suffer from a coronary heart disease more than a year participated in this study. In depth interviews and field notes were used to collect data. The results showed that subjects perceived their illness differently. Subject I perceived illness as a test; Subject II perceived illness as a reminder of own weakness; whereas Subject III perceived illness as a warning, absolution, and feeling to be loved by others. The core meaning found in this study is that persons who are able to give meaning to their illness have their optimism for recovery. It can be concluded that illness is a physical as well as a psychological condition; individual respond to symptom of illness differently; and meaning given to illness is subject to change due to the affected person’s situation.